Antioxidant properties of Moringa oleifera and Withania somnifera extracts and their use in cosmetics for men - Jezierska, Adrianna; Sykuła, Anna (Wydawnictwo Politechniki Łódzkiej, 2023)
Nowadays, men are paying more and more attention to their appearance, and thus try to provide their skin with proper care so that it looks healthy and without signs of aging. In the present study, ashwagandha (Withania somnifera) and moringa oleifera (Moringa oleifera) were selected from the most popular adaptogens used in cosmetics, which are currently not commonly used in cosmetic preparations for men. The selected adaptogens were compared for their phytochemical and antioxidant properties to determine their skin care effects in cosmetics. The phytochemical content was evaluated through the determination of total phenolic content and in vitro antioxidant capacity was determined by DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS{2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid)} free radical scavenging tests. The total phenolic contents 1.81±0.13 and 0.14±0.02 mg GAE/g extract were found to be present in Moringa oleifera and Withania somnifera glycol-water extracts, respectively. Among the two chosen extracts, Moringa oleifera exhibited significant free radical scavenging activity, ABTS (0.964 ± 0.021 mg TE/g extract) and DPPH (0.822 ± 0.004 mg TE/g extract). It can be concluded that Moringa oleifera extract has strong antioxidant properties than Withania somnifera extract.
Keywords: extracts; antioxidants; Moringa oleifera; Withania somnifera; cosmetics for men; polyphenol; ekstrakty; przeciwutleniacze; kosmetyki dla mężczyzn; polifenol